2018
DOI: 10.1108/bfj-04-2017-0215
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of organic food buyers: an emergent market perspective

Abstract: Purpose The purpose of this paper is to obtain empirical understanding of organic food buyers in the context of emergent organic food market (i.e. Bosnia and Herzegovina) by using a segmentation approach. Design/methodology/approach A self-administrated online survey was carried out among organic food buyers (n=202) using the snowball sampling technique. Measurement items were mainly adapted from the prior studies. Findings The authors analysed the heterogeneity of organic food buyers with latent class mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 75 publications
1
22
0
1
Order By: Relevance
“…The influence of knowledge on consumer’s buying behaviour and purchase intentions of OFP has also been identified by Rana and Paul (2017). Additionally, results found for Lisbon were also similar to other OFP emerging markets (Le‐Anh & Nguyen‐To, 2020; Peštek, Agic, & Cinjarevic, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…The influence of knowledge on consumer’s buying behaviour and purchase intentions of OFP has also been identified by Rana and Paul (2017). Additionally, results found for Lisbon were also similar to other OFP emerging markets (Le‐Anh & Nguyen‐To, 2020; Peštek, Agic, & Cinjarevic, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Considering the fact that that demographic analysis did not provide the information needed for successful targeting of organic food consumers, many authors applied segmentation analysis in order to identify the characteristics of different segments of organic food consumers. The results revealed that the same segments of organic food consumers cannot be found in all investigated markets, i.e., that organic food consumers have different demographic, psychographic, and behavioral characteristics, observed in different markets and different countries [9,20,25,26]. Therefore, different studies were conducted regarding consumer perception and barriers that prevent them from buying these products in order to better understand what drives the consumption of organic products.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Actually it is not possible to define precisely all the dimensions related to this offer. Scholars are still working to provide valid information on strategic aspects such as the market segmentation (Hansen et al, 2018;Peštek et al, 2018;Sultan et al, 2018), the role of awareness (Asif et al, 2018), the willingness to pay higher prices (Aschemann-Witzel, and Zielke, 2017), the country of origin (Thøgersen et al, 2017), the relationship with health concern (Apaolaza et al, 2018) or the perspectives on production (Popović et al, 2018). Analyzing the evidences from the market, increasing sales are registered.…”
Section: The Eco-label Frameworkmentioning
confidence: 99%